Mandatory Basic Health Insurance in Segmented Markets - Beteta, Edmundo (Estudios de Economía, 2016)
We analyze the effect of introducing a minimum mandatory health insurance planin a segmented market in which high risks are affiliated to the public insurer andlow risks to the private ones (market segmentation is endogenously obtainedin our model). We assume both types of insurers must provide the basic plan,insurance is compulsory, and there is a minimum premium regulation. When wecompare the equilibriums pre and post introduction of the basic health insuranceplan, we find that an implicit subsidy mechanism operates that gives somesolidarity to the system, even though no explicit risk compensation mechanismis introduced. For this implicit subsidy mechanism to operate, it is fundamentalthat not only the price of the basic plan is regulated but also the quality of theservices included in such plan, and that the regulator is able to guarantee privateinsurers do offer the minimum plan to all risks.